FreeSWITCH 1.6 cookbook : over 45 practical recipes to empower you with the latest FreeSWITCH 1.6 features /: over 45 practical recipes to empower you with the latest FreeSWITCH 1.6 features. (2015) - II, Minessale, Anthony; Maruzzelli, Giovanni; Collins, Michael (Michael S.)
No abstract available